Analisis Kebijakan Madrasah di MAN 1 Pekalongan Berdasarkan (SKB 3 Menteri Tahun 1975, UU No 20 Tahun 1989, UU No 20 Tahun 2003): - Santoso, Achmad Erwin (LPPM Institut Pendidikan Nusantara Global, 2025)
This study aims to analyze madrasah policies at MAN 1 Pekalongan based on three main legal bases, namely the 1975 Joint Decree of 3 Ministers, Law No. 20 of 1989 concerning the National Education System, and Law No. 20 of 2003 concerning the National Education System. This study uses a qualitative approach with a descriptive analytical method, involving document review and interviews with related parties at MAN 1 Pekalongan. The results of the study indicate that madrasah policies at MAN 1 Pekalongan are in line with the principles stated in the 1975 Joint Decree of 3 Ministers, which emphasize the integration of religious and general curriculum. In addition, the implementation of the policy also meets the standards stipulated in Law No. 20 of 1989, especially regarding the management of educational institutions with Islamic characteristics. Furthermore, based on Law No. 20 of 2003, the policies at MAN 1 Pekalongan support the implementation of competency-based education by considering local and global relevance. This study concludes that the madrasah policy at MAN 1 Pekalongan is able to accommodate national regulations while strengthening the characteristics of madrasahs as modern Islamic educational institutions. However, it is necessary to strengthen the synergy aspect between local and national regulations to improve the quality of education more holistically.